PENGARUH KOMITMEN ORGANISASI DAN KEPERCAYAAN DIRI TERHADAP AKUNTABILITAS KERJA KEPALA SEKOLAH SEKOLAH DASAR KECAMATAN JONGGAT (STUDI ANALISIS JALUR) - SUHARDI, MUHAMAD (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2024)
This research aims to determine the influence of organizational commitment and self-confidence on the work accountability of elementary school principals in Jonggat sub-district, Central Lombok Regency, odd semester of the 2023/2024 academic year. This research uses a survey research method involving causality studies. The researcher involved three variables originating from the same respondent who were answered simultaneously and simultaneously. The population in this study were all principals of state and private elementary schools in the Jonggat sub-district, Central Lombok, totaling 35. The sample choice for principals was public elementary schools and private elementary schools, which was carried out using purposive random sampling. This research examines one exogenous variable and one endogenous variable. Each variable is measured using a questionnaire technique which is arranged in the form of question items which are built based on the theoretical basis, dimensions and indicators of each variable. The hypothesis tested in this research is: the occurrence of a causal relationship between research variables X1, X2, X3. To test this hypothesis, path analysis was carried out. The research results are as follows: Hypothesis testing shows that there is a strong influence between the variables Organizational Commitment on Self-Confidence, which produces a correlation determinant coefficient of 0.875, which means that the contribution of Organizational Commitment to Self-Confidence is 87.5% and the remaining 12.5% ??is not included in the model . The path coefficient for Organizational Commitment on Self-Confidence is 0.936 and the p-value is 0.00 <0.05, which means that there is a very significant influence between Organizational Commitment (X1) on Self-Confidence (X2). Hypothesis testing shows that there is an influence between the variables Organizational Commitment (X1) and Self-Confidence (X2) on the Principal's Work Accountability (X3), which is indicated by the coefficient of determination value of 0.937. This figure illustrates that the contribution of Organizational Commitment (X1) and Self-Confidence (X2) to Principal Work Accountability (X3) is 93.7% while the remaining 6.3% is not included in the model. Based on the results of hypothesis testing, it can be concluded that all alternative hypotheses proposed can be significantly accepted. ABSTRAKPenelitian ini bertujuan untuk mengetahui pengaruh komitmen organisasi dan kepercayaan diri terhadap akuntabilitas kerja kepala sekolah SD se-kecamatan Jonggat Kabupaten Lombok Tengah semester gannjil tahun pelajaran 2023/2024. Penelitian ini menggunakan metode penelitian survey yang melibatkan studi kausalitas. peneliti melibatkan tiga variabel yang berasal dari satu responden yang sama yang dijawab secara serentak dan sekaligus. Populasi dalam penelitian ini adalah seluruh Kepala Sekolah Dasar (SD) Negeri dan Swasta se-kecematan Jonggat Lombok Tengah yang berjumlah 35. Pilihan sampel Kepala Sekolah yaitu SD negeri dan SD Swasta yang dilakukan dengan purposive random sampling. Penelitian ini meneliti satu variabel exogenus dan satu variabel endogenus. Masing-masing variabel diukur dengan menggunakan teknik kuesioner yang disusun dalam bentuk butir-butir pertanyaan yang dibangun berdasarkan landasan teori, dimensi dan indikator masing-masing variabel. Hipotesis yang diuji dalam penelitian ini adalah: terjadinya hubungan kausal antar variabel penelitian X1, X2, X3. Untuk meguji hipotesis ini dilakukan analisis jalur. Hasil penelitian sebagai berikut: Pengujian hipotesis menunjukkan terdapat pengaruh yang kuat diantara variabel Komitmen Organisasi terhadap Percaya Diri, yang menghasilkan koefisien determinan korelasi sebesar 0,875 yang artinya kontribusi Komitmen Organisasi terhadap Percaya Diri sebesar 87,5% dan sisanya 12,5% tidak masuk dalam model. Koefisien jalur Komitmen Organisasi terhadap Percaya Diri 0,936 dan p-value 0.00 < 0.05 yang artinya bahwa ada pengaruh yang sangat signifikan antara Komitmen Organisasi (X1) terhadap Percaya Diri (X2). Pengujian hipotesis menunjukkan bahwa terdapat pengaruh antara variabel Komitmen Organisasi (X1) dan Percaya Diri (X2) terhadap Akuntabilitas Kerja Kepala Sekolah (X3), yang ditunjukan dengan nilai koefisen determinasi sebesar 0,937. Angka tersebut menggambarkan bahwa kontribusi Komitmen Organisasi (X1) dan Percaya Diri (X2) terhadap Akuntabilitas Kerja Kepala Sekolah (X3) sebesar 93,7% sedangkan sisanya 6,3% tidak termasuk dalam model. Berdasarkan hasil pengujian hipotesis dapat disimpulkan bahwa seluruh hipotesis alternatif yang diajukan dapat diterima secara signifikan.